Child-friendly Pesantren in Indonesia: hopes and realities - Natsir, Albert; Sesmiarni, Zulfani; Hanani, Silfia (Penerbit Universiti Kebangsaan Malaysia, 2023)
This research describes the results of the evaluation of the child-friendly Pesantren program in West Sumatra Province Indonesia. The model used by CIPP is the Mixed Method. Data collection techniques used questionnaires, observation sheets, interviews, concept mastery tests, and guidelines for child-friendly pesantren. Data analysis and program evaluation procedures are described in this article. The results of the context evaluation show that violence, discrimination, and harassment still occur in the average pesantren in the province of West Sumatra. The results of the input evaluation show that the guidelines for the child-friendly pesantren program issued by the Ministry of Religion, the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia have not been optimally socialized and the pesantren leaders, asatidz councils, students and the community are aware of the existence of a child-friendly pesantren program but do not yet understand the concepts, guidelines and technical instructions for child-friendly pesantren. The results of the process evaluation, namely monitoring designed to reveal the strengths and weaknesses of the implementation of the child-friendly pesantren program have not been optimal. Not all Pondok pesantren have a child-friendly boarding school development team. For pesantren that already have a child-friendly pesantren team, the team members do not yet have the relevant competencies. Evaluation of products or outputs and results designed to assess program results and program sustainability shows that the child-friendly pesantren program launched and developed by the government and Pondok pesantren has not run as expected.